2018
DOI: 10.3389/fnagi.2018.00110
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Tai Chi Intervention on Healthy Elderly by Means of Neuroimaging and EEG: A Systematic Review

Abstract: Aging is a process associated with a decline in cognitive and motor functions, which can be attributed to neurological changes in the brain. Tai Chi, a multimodal mind-body exercise, can be practiced by people across all ages. Previous research identified effects of Tai Chi practice on delaying cognitive and motor degeneration. Benefits in behavioral performance included improved fine and gross motor skills, postural control, muscle strength, and so forth. Neural plasticity remained in the aging brain implies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 55 publications
0
14
0
1
Order By: Relevance
“…Fifth, tai chi is considered to be a mind–body exercise ( Tao et al, 2017a ); it is therefore not possible to examine which activity—physical or mental—promotes the functional improvements reported here. Finally, studies show that tai chi affects hemispheric reorganization, such as modified brain activity, functional connectivity, and brain structures, in older adults ( Pan et al, 2018 ). Thus, in future studies, the application of advanced neuroimaging techniques and electroencephalography focused on the underlying mechanisms of cognitive and motor benefits is desirable.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, tai chi is considered to be a mind–body exercise ( Tao et al, 2017a ); it is therefore not possible to examine which activity—physical or mental—promotes the functional improvements reported here. Finally, studies show that tai chi affects hemispheric reorganization, such as modified brain activity, functional connectivity, and brain structures, in older adults ( Pan et al, 2018 ). Thus, in future studies, the application of advanced neuroimaging techniques and electroencephalography focused on the underlying mechanisms of cognitive and motor benefits is desirable.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that different forms of PA, including mind-body training [49,50,51,52,53,54,55] as well as mindfulness practices [56,57,58,59], can modulate electrical brain activity. To uncover the potential underlying electrophysiological mechanisms of QMT-induced cognitive changes, EEG power and coherence were first examined.…”
Section: Qmt Effects: Neuropsychological Researchmentioning
confidence: 99%
“…To the best of our knowledge, there is no systematic review or meta-analysis study that has integrated findings focused on different types of mind–body exercise as a whole. Previous systematic reviews on TCC [ 24 ] and yoga [ 19 , 25 ], were based on a small number of studies and did not focus on specific brain regions or networks affected by mind–body exercise. In the present study, we conducted a systematic review of MRI-based studies investigating the relationship between mind–body exercise and brain structure and function to elucidate the possible neural mechanisms underlying the health benefits of mind–body exercises.…”
Section: Introductionmentioning
confidence: 99%